STRUCTURAL- MORPHOLOGICAL CHARACTERISTICS OF BINARY TAUTOLOGISMS - Saidova Kamola Ilhomjonovna; Olimzoda Parvina (International Journal on Orange Technologies, 2020)
This article is about comparison of structural- morphological characteristics of binary tautologizms in two languages and they are given with examples. And also is given and discussed types of nominative phraseological units